Determinants and Macroeconomic Impact of Remittances in Sub-Saharan Africa - Singh, Raju Jan; Haacker, Markus; Lee, Kyung-woo; Le Goff, Maelan (2012)
This paper investigates the determinants and the macroeconomic role of remittances in sub-Saharan Africa. It assembles the most comprehensive data set available so far on remittances in the region; it comprises data for 36 countries for 1990 through 2008, and incorporates newly available data on the size and location of the diaspora. We find that remittances are larger for countries with a larger diaspora or when the diaspora is located in wealthier countries, and that they behave counter-cyclically, consistent with a role as a shock absorber. Although the effect of remittances in growth regressions is negative, countries with well functioning domestic institutions seem nevertheless to be better at unlocking the potential for remittances to contribute to faster economic growth.